2020
DOI: 10.1097/md.0000000000023506
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity predicts higher healthcare costs among hospitalized nonalcoholic fatty liver disease/nonalcoholic steatohepatitis (NAFLD/NASH) patients in Spain

Abstract: The rising prevalence of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) presents many public health challenges, including a substantial impact on healthcare resource utilization and costs. There are important regional differences in the burden of NAFLD/NASH, and Spain-specific data are lacking. This retrospective, observational study examined the impact of liver disease severity, comorbidities, and demographics on healthcare resource utilization and costs in Spain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Nonalcoholic fatty liver disease (NAFLD) is highly prevalent [1][2][3] and exerts tremendous economic strain on the world economy. [4][5][6] This condition is progressive, may lead to steatohepatitis, and has been linked to cardiovascular disease, diabetes, cirrhosis, and cancer. Steatosis, a hallmark and initiating pathogenic feature, represents fat droplets in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is highly prevalent [1][2][3] and exerts tremendous economic strain on the world economy. [4][5][6] This condition is progressive, may lead to steatohepatitis, and has been linked to cardiovascular disease, diabetes, cirrhosis, and cancer. Steatosis, a hallmark and initiating pathogenic feature, represents fat droplets in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The economic model has been largely informed by data from the resmetirom phase II trial in patients with NASH and stage 1-3 fibrosis [18]; in particular, the baseline patient characteristics and the initial distribution of patients across fibrosis health states used in the model. Multiple studies have highlighted the global economic burden associated with NASH and NAFLD [7][8][9][10][11][12], and a clinically beneficial and potentially cost-effective treatment such as resmetirom may reduce this burden.…”
Section: Discussionmentioning
confidence: 99%
“…20 years in the US [7]. Further global studies have demonstrated the significant costs associated with the condition, particularly in the latter stages of disease [8][9][10][11][12].…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
See 1 more Smart Citation
“…Both dietary interventions in this SR are in accordance with EASL, ESPEN, AGA, and AASLD guidelines, where a hypocaloric or the Mediterranean diet is suggested as a dietary treatment for NAFLD. However, current guidelines do not address the optimal dietary strategy specifically for active, fibrotic, and cirrhotic NASH, although it contributes to the overall burden of the disease, not only on the t point of view of patients but also economically on the public health (77)(78)(79)(80). Due to this burden, different stages, especially active and fibrotic NASH, cannot be disregarded when designing future studies.…”
Section: Discussionmentioning
confidence: 99%